Effect of organophosphorus pesticide exposure on the immune cell phenotypes among farm women and their children. Issue 9 (9th September 2022) - Medithi, Srujana; Kasa, Yogeswar Dayal; Ajumeera, Rajanna; Jee, Babban; Kodali, Venkaiah; Jonnalagadda, Padmaja R.
Abstract: Epidemiological studies suggest suppression of the lymphocytes function through cholinergic stimulation due to organophosphorus pesticide exposure. The study aimed to assess the alteration in the levels of immune cell phenotypes among farm women (FW) and farm children (FC) who were occupationally exposed to pesticides and age/gender-matched control subjects belonging to Rangareddy district (Telangana, India). A total of 129 FW, 129 FC and 268 age/gender-matched controls were recruited. Blood samples were collected from the selected subjects to estimate the levels of nine organophosphorus pesticide residues and CD (CD3+, CD4+, CD8+, CD16+ and CD19+) cell markers using LC-MS/MS and flow cytometry, respectively. Independent t -test analysis was conducted to compare the immune cell phenotypes between exposed and control groups. Spearman's rank correlation test was further carried out to identify any possible correlation between the pesticide residues and CD markers. The mean percentage for CD4+, CD8+ and CD16+ was found to be significantly low, while for CD19 + itwas significantly high in the FW as compared to the CW group ( p < 0.01). Further, the residues of chlorpyrifos and monocrotophos among FW were found to be significantly correlating with the mean percentages of CD19+ and CD8+ markers, respectively. The cell marker subsets of CD4+ and CD8+ were significantly low in FC children 9–12 years and 13–15 years age groups, respectively ( p < 0.05). Also, these levels were significantly correlating with the residues of malathion and monocrotophos. The present study could indicate an alteration in the lymphocytes' subpopulations, which may thereby infer the toxicity in the first phase assessment of immunotoxicity. Therefore, further studies may be conducted to understand the suspected pesticides' mechanism along with various other factors in causing immune suppression coupled with nutritional and other related disorders.